Development of Lidocaine-Loaded Dissolving Microneedle for Rapid and Efficient Local Anesthesia - Huisuk Yang; Geonwoo Kang; Mingyu Jang; Daniel Junmin Um; Jiwoo Shin; Hyeonjun Kim; Jintae Hong; Hyunji Jung; Hyemyoung Ahn; Seongdae Gong; Chisong Lee; Ui-Won Jung; et al. (MDPI AG, 2020)
Lidocaine is a local anesthetic agent used in the form of injection and topical cream. However, these formulation types have limitations of being either painful or slow-acting, thereby hindering effective and complete clinical performance of lidocaine. Dissolving microneedles (DMNs) are used to overcome these limitations owing to their fast onset time and minimally invasive administration methods. Using hyaluronic acid and lidocaine to produce the drug solution, a lidocaine HCl encapsulated DMN (Li-DMN) was fabricated by centrifugal lithography. The drug delivery rate and local anesthetic quality of Li-DMNs were evaluated using the pig cadaver insertion test and Von Frey behavior test. Results showed that Li-DMNs could deliver sufficient lidocaine for anesthesia that is required to be utilized for clinical level. Results from the von Frey test showed that the anesthetic effect of Li-DMNs was observed within 10 min after administration, thus confirming fast onset time. A toxicity test for appropriate clinical application standard was conducted with a microbial limit test and an animal skin irritation test, showing absence of skin irritation and irritation-related microorganisms. Overall, Li-DMN is a possible alternative drug delivery method for local anesthesia, meeting the requirements for clinical conditions and overcoming the drawbacks of other conventional lidocaine administration methods.